Frameshift mutational target gene analysis identifies similarities and differences in constitutional mismatch repair‐deficiency and Lynch syndrome. Issue 7 (30th March 2017) - Maletzki, Claudia; Huehns, Maja; Bauer, Ingrid; Ripperger, Tim; Mork, Maureen M.; Vilar, Eduardo; Klöcking, Sabine; Zettl, Heike; Prall, Friedrich; Linnebacher, Michael
Abstract : Mismatch‐repair deficient (MMR‐D) malignancies include Lynch Syndrome (LS), which is secondary to germline mutations in one of the MMR genes, and the rare childhood‐form of constitutional mismatch repair‐deficiency (CMMR‐D); caused by bi‐allelic MMR gene mutations. A hallmark of LS‐associated cancers is microsatellite instability (MSI), characterized by coding frameshift mutations (cFSM) in target genes. By contrast, tumors arising in CMMR‐D patients are thought to display a somatic mutation pattern differing from LS. This study has the main goal to identify cFSM in MSI target genes relevant in CMMR‐D and to compare the spectrum of common somatic mutations, including alterations in DNA polymerases POLE and D1 between LS and CMMR‐D. CMMR‐D‐associated tumors harbored more somatic mutations compared to LS cases, especially in the TP53 gene and in POLE and POLD1, where novel mutations were additionally identified. Strikingly, MSI in classical mononucleotide markers BAT40 and CAT25 was frequent in CMMR‐D cases. MSI‐target gene analysis revealed mutations in CMMR‐D‐associated tumors, some of them known to be frequently hit in LS, such as RNaseT2, HT001, and TGFβR2 . Our results imply a general role for these cFSM as potential new drivers of MMR‐D tumorigenesis.